ANALYSIS OF ARABICA COFFEE COMMODITIES BUSINESS MODELS AND IMPLEMENTATION OF THE GREEN MSME CONCEPT IN BENER MERIAH DISTRICT - Dedy Darmansyah; Hartini; Ina Yuyun; Abdillah Rasyid (CV. Radja Publika, 2023)
In a global era that increasingly emphasizes the issue of climate change and environmental sustainability, Micro, Small and Medium Enterprises (MSMEs) have a crucial role in combining economic growth with environmental preservation. Bener Meriah Regency, as one of the leading Arabica coffee producers in Indonesia, has a golden opportunity to adopt the green MSME model in the coffee business. This business model emphasizes the application of green technology and a circular economy that optimizes the use of resources. This research was conducted in Bener Meriah Regency during the period June to September 2023, using the Business Model Canvas method and the green business concept from Bank Indonesia. The research results show that Arabica coffee MSMEs in Bener Meriah Regency have started implementing a green business model with a focus on various aspects, including production, marketing, human resources, and finance. In addition, the adoption of this business model is reinforced by the principles of green entrepreneurship, where sustainability is a core part of business operations. This gives a positive indication of the potential of MSMEs in Bener Meriah Regency to contribute to creating a more sustainable and environmentally friendly economy.